Exploring the Impact of Early Exposure to Research on Dual Enrollment Students: A Qualitative Single-Case Study (Journal of Applied Learning and Teaching, 2021)
Embry-Riddle Aeronautical University (ERAU) provides a concurrent enrollment model to high schools across the United States.  The concurrent enrollment opportunity offers science, technology, engineering, and mathematical (STEM) college-credit coursework taught by college-credentialed instructors on the student’s high school campus. One faculty member transitioned to Embry-Riddle’s main residential campus following seven years of service with ERAU's concurrent enrollment program. During his tenure with ERAU's concurrent enrollment program, in addition to instructing a variety of concurrent enrollment courses, he maintained an active research agenda that involved concurrently enrolled students. His transition was preceded by the matriculation of a subset of these students to Embry-Riddle’s main campus. Each of these students immediately reengaged in undergraduate research with the faculty member while he continued to serve in a strong mentoring role. This presentation explores the affect this opportunity had on individual members of this tight-knit cohort as they progressed through their concurrent enrollment and undergraduate studies, participated in a long-standing mentoring relationship, and undertook their post-graduation decision-making. The research showcases project-based learning as a scaffolding technique for meaningful undergraduate research and how it may illuminate a pathway for students who do not initially see STEM as a viable option.